How the Antimicrobial Peptides Kill Bacteria: Computational Physics Insights (Communications in Computational Physics, 2012)
In the present article, coarse grained Dissipative Particle Dynamics simulation with implementation of electrostatic interactions is developed in constant pressureand surface tension ensemble to elucidate how the antimicrobial peptide molecules affect bilayer cell membrane structure and kill bacteria. We find that peptides with different chemical-physical properties exhibit different membrane obstructing mechanisms.Peptide molecules can destroy vital functions of the affected bacteria by translocating across their membranes via worm-holes, or by associating with membrane lipidsto form hydrophilic cores trapped inside the hydrophobic domain of the membranes.In the latter model, the affected membranes are strongly buckled, in accord with veryrecent experimental observations [G. E. Fantner et al., Nat. Nanotech., 5 (2010), pp. 280-285].